2019
DOI: 10.1021/acs.langmuir.8b03674
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Characterization of 1,2-Dipalmitoyl-sn-glycero-3-cytidine Diphosphate Nucleolipid Monolayer Supported on Gold (111) Electrode

Abstract: The effect of the electrode potential on the orientation and conformation of the 1,2-dipalmitoyl-sn-glycero-3cytidine monolayer deposited on a gold (111) electrode surface was described. The potential of zero free charge (E pzc ) for the monolayer-covered electrode was determined to be −0.2 V vs SCE. The differential capacitance and charge density data indicated that the monolayer is stable at the electrode surface when (E − E pzc ) > 0.0 V. At negative rational potentials, a progressive detachment (electrodew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Several studies with nucleolipid monolayers formed at the air water interphase demonstrated molecular recognition capabilities of these monolayers to the complementary DNA bases [10][11][12][13][14][15][16][17]. Our work with 16:0 DG-CDP monolayers on gold electrodes, previously incubated with guanine in 0.1 M NaF solutions, showed the existence of specific Watson-Crick interactions between the cytosine moiety of the nucleolipid and guanine at positive electrode charge densities and non-specific interactions at negatively charged surfaces [18]. This knowledge could be used for the preparation of functionalized liposomes for drug delivery.…”
Section: -Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Several studies with nucleolipid monolayers formed at the air water interphase demonstrated molecular recognition capabilities of these monolayers to the complementary DNA bases [10][11][12][13][14][15][16][17]. Our work with 16:0 DG-CDP monolayers on gold electrodes, previously incubated with guanine in 0.1 M NaF solutions, showed the existence of specific Watson-Crick interactions between the cytosine moiety of the nucleolipid and guanine at positive electrode charge densities and non-specific interactions at negatively charged surfaces [18]. This knowledge could be used for the preparation of functionalized liposomes for drug delivery.…”
Section: -Introductionmentioning
confidence: 51%
“…Electrochemical and PM-IIRAS instrumentation and measurements has been described thoughtfully in a previous work. [9]. A detailed description is also included in the supplementary information file.…”
Section: -Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, PM‐IRRAS allows the investigation of how water cushion formation separates a phospholipid bilayer from the electrode surface influencing the membrane orientation and ET processes [110,111] . Capacitance and chronocoulometric measurements coupled with PM‐IRRAS are effective for probing the stability of the lipid monolayer on electrodes and determining the conformation and orientation of acyl chains as a function of applied potentials [112–114] as well as for studying ion channel properties, lipid‐peptide interactions, and transmembrane ion transport mechanisms [115–117] . Recently, Su et al [115] .…”
Section: Biospectroelectrochemistry Through Membranes and Cellsmentioning
confidence: 99%